2017
DOI: 10.1007/s00234-017-1850-y
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment in patients with carotid artery dissection and intracranial occlusion: a systematic review

Abstract: PurposeRecently, multiple randomised controlled trials showed efficacy of endovascular treatment over traditional care in patients with acute ischemic stroke due to an intracranial anterior circulation occlusion. Internal carotid artery (ICA) dissection with a concomitant intracranial occlusion is a rare but important cause of severe acute ischemic stroke. Although this subtype of acute ischemic stroke is mostly treated with endovascular treatment, treatment outcomes are still sparsely studied. This study asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
(44 reference statements)
4
16
0
1
Order By: Relevance
“…Furthermore, the rate of symptomatic ICH was not higher in patients with CAD, despite our finding that CAD patients suffered from larger occlusions (more distal ICA and ICA-T occlusions) and had a lower ASPECTS score at baseline. Our finding that the rate of complications in EVT-treated patients with CAD is not increased, corresponds with previous research (18, 19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the rate of symptomatic ICH was not higher in patients with CAD, despite our finding that CAD patients suffered from larger occlusions (more distal ICA and ICA-T occlusions) and had a lower ASPECTS score at baseline. Our finding that the rate of complications in EVT-treated patients with CAD is not increased, corresponds with previous research (18, 19).…”
Section: Discussionsupporting
confidence: 93%
“…This can be explained by the fact that patients with CAD were younger and had less cardiovascular risk factors. These findings are consistent with a recent systematic review that showed that a large proportion of patients with tandem occlusion due to CAD achieved functional independency after EVT (18). Furthermore, we observed longer procedural times and lower rates of successful reperfusion in patients with CAD and ACAO.…”
Section: Discussionsupporting
confidence: 92%
“…The American College of Radiology recommends that among those with suspected stroke who developed a new focal neurologic deficit, fixed or worsening, in conjunction with MRI of the head, a non-contrast head MRA and contrast-enhanced neck MRA be performed [10]. A systematic review of 16 studies suggested that endovascular treatment for carotid dissection and concomitant proximal intracranial occlusion, using any or combinations of intra-arterial thrombolytic therapy, angioplasty or stenting, was associated with favourable outcome and successful reperfusion; however, the authors warned that most of the included studies had a high risk of bias [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hoving et al have advised further analysis of treatment trials to assess its therapeutic effectiveness 27…”
Section: Discussionmentioning
confidence: 99%